Peran Guru PAK dalam Perencanaan Pembelajaran untuk Meningkatkan Karakter Siswa (Jurnal Pendidikan Agama dan Teologi, 2024)
Learning planning in Christian religious education has a significant role in shaping student character based on Christian values. Christian religious education teachers provide guidance for students in understanding the values ​​of faith such as love, justice, humility, forgiveness, and service to others, apart from just being teachers. This research uses a descriptive qualitative approach by carrying out a literature review to find the role played by Christian religious education teachers in developing the learning process. From the research results, it was revealed that effective learning planning is able to provide support for students in understanding and applying religious values ​​in their daily activities. However, teachers face several challenges, such as limited resources, lack of adequate training, resistance to change, and difficulties in implementing online learning. Improving teacher skills, utilizing technology, creating relevant modules, and collaboration between schools are key elements in the proposed solution. By applying the latest appropriate strategies, Christian religious education teachers can create effective learning experiences to guide a generation with good morals in accordance with Christian principles and ready to face the dynamics of ever-changing times.